Pearl Grey Shading Net Boosts the Accumulation of Total Carotenoids and Phenolic Compounds That Accentuate the Antioxidant Activity of Processing Tomato - Luigi Formisano; Michele Ciriello; Christophe El-Nakhel; Milena Poledica; Giuseppe Starace; Giulia Graziani; Alberto Ritieni; Stefania De Pascale; Youssef Rouphael (MDPI AG, 2021)
Tomato (Solanum lycopersicum L.) is one of the most consumed vegetables worldwide due to its low caloric intake and high fiber, minerals, and phenolic compounds, making it a high-quality functional food. However, fruit quality attributes can be affected by pre-harvest factors, especially environmental stresses. This research aimed to evaluate the influence of two shading nets (white net −30% and pearl grey net −40% shading degree) on the yield and phytochemical profile of tomato fruits grown in summer under the Mediterranean climate. Mineral and organic acid content (by ion chromatography-IC), phenolic profile (by ultra-high performance liquid chromatography-UHPLC coupled with an Orbitrap high-resolution mass spectrometry-HRMS), carotenoid content (by high-performance liquid chromatography with diode array detection-HPLC-DAD), and antioxidant activities DPPH, ABTS, and FRAP (by UV-VIS spectrophotometry) were determined. Tomato fruits grown under the pearl grey net recorded the highest values of total phenolic compounds (14,997 µg 100 g−1 of fresh weight) and antioxidant activities DPPH, ABTS, and FRAP, without affecting either fruit color or marketable yield. The reduction of solar radiation through pearl grey nets proved to be an excellent tool to increase the phytochemical quality of tomato fruits during summer cultivation in a Mediterranean environment.